(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the treatment costs of Thalassemia and Hemophilia at both basic and specialized levels in order to estimate the financial burden associated with these rare diseases. Methods: A cross-sectional study using 2023 health-insurance reimbursement data from the National Institute of Hematology and Blood Transfusion (NIHBT) and Ha Dong General Hospital. Results: The average inpatient cost per episode for Thalassemia at NIHBT was VND 8,426,852, lower than the VND 9,760,068 recorded at Ha Dong General Hospital. Corresponding outpatient costs were VND 3,452,519 and VND 3,267,405, respectively. Among Hemophilia patients treated at Ha Dong General Hospital, mean inpatient cost reached VND 16,920,358 per episode, while outpatient care cost only VND 39,345. Health insurance covered 95 – 100 % of total costs, yet patients at the provincial level still had to co-pay an average of VND 400,000 – 500,000 for each inpatient episode. The bulk of expenditures was concentrated on drugs, blood products, and infusions. Conclusion: These findings reveal a substantial financial burden on patients with the rare diseases Thalassemia and Hemophilia. The amended Health Insurance Law (No. 51/2024/QH15), effective 1 January 2025, which mandates 100 % coverage at the basic level for both conditions, constitutes an important advance toward equity and the reduction of out-of-pocket costs for this patient group.